MODEL OPERASIONALISASI LEMBAGA INTERMEDIASI DALAM PENCIPTAAN INFRASTRUKTUR SERTIFIKASI KOMPETENSI DI JAWA TENGAH - Dewi, Yustina Ertie Pravitasmara (Faculty of Economics Universitas Atma Jaya Yogyakarta, 2016)
This study aimed to assess the development model of BKSP (Coordinating Board ofProfessional Certification) as an intermediary institution in the creation of infrastructurecompetence of human resources in Central Java. Availability of infrastructure inestablishing certificate of competency is the main requirement to conduct a competencybased assessment that expected to increase the competitiveness of Indonesia in the ASEANsingle market community. As a descriptive qualitative research, data used are primarydata obtained from 40 interviewees in Central Java in 2010. The resulting model in thestudy showed a coordination role in combining the stakeholders in a concerted effort toincrease the number of certified workers.Keywords: competency based assessment, certificate of competency, human resources